May we be spared to meet on earth : letters of the lost Franklin Arctic expedition - Potter, Russell A., 1960-; Koellner, Regina; Carney, Peter (Blogger); Williamson, Mary (Descendent of Sir John Franklin) (McGill-Queen's University Press, 2022)
"May We Be Spared to Meet on Earth is a privileged glimpse into the private correspondence of the officers and sailors who set out in May 1845 on the Erebus and Terror for Sir John Franklin's fateful expedition to the Arctic. The letters of the crew and their correspondents begin with the journey's inception and early planning, going on to recount the ships' departure from the river Thames, their progress up the eastern coast of Great Britain to Stromness in Orkney, and the crew's exploits as far as the Whalefish Islands off the western coast of Greenland, from where the ships forever departed the society that sent them forth. As the realization dawned that something was amiss, heartfelt letters to the missing were sent with search expeditions; those letters, returned unread, tell poignant stories of hope. Assembled completely and conclusively from extensive archival research, including in far-flung family and private collections, the correspondence allows the reader to peer over the shoulders of these men, to experience their excitement and anticipation, their foolhardiness, and their fears. The Franklin expedition continues to excite enthusiasts and scholars worldwide. May We Be Spared to Meet on Earth provides new insights into the personalities of those on board, the significance of the voyage as they saw it, and the dawning awareness of the possibility that they would never return to British shores or their families."--